Heat transfer analysis of a data centre / Kabildev Arumainathan - Kabildev , Arumainathan (2020)
Data centres are an integral part of networking as it houses servers that facilitate incoming and outgoing data flow. A resolute cooling approach is needed to overcome the hot air dissipated by these servers. This research focused on the computational fluid dynamics (CFD) simulation of the heat transfer modelled upon Telekom Malaysia (TM) City’s data centre 3. The simulation was carried out to ascertain the heat distribution across the data centre by using ANSYS Fluent. The results indicated that the server racks’ inlet temperature reaches 29.79 oC, which is close to the maximum permissible limit according to recommendations provided by the American Society of Heating, Refrigerating and Air-Conditioning Engineers (ASHRAE). The temperature level was elevated due to exhaust air recirculating from the hot aisles into the cold aisles. This issue was addressed by equipping a cold air containment system (CACS). The findings demonstrated a decline in maximum temperature at the front portion of the server racks to 26.98 oC and the temperature was spread more homogenously. Correspondingly, the hot air recirculation issue was surmounted by the CACS. Overall, the cooling of the servers was substantially improved with the containment system in place.